Bisphenols A and F, but not S, induce apoptosis in bovine granulosa cells via the intrinsic mitochondrial pathway - Kourmaeva, Emilia; Sabry, Reem; Favetta, Laura A. (Frontiers in Endocrinology, 2022)
With the gradual decline in global fertility rates, there is a need to identify potential contributing factors, their mechanisms of actions and investigate possible solutions to reverse the trend. Endocrine disrupting compounds (EDCs), such as bisphenol A (BPA), are environmental toxicants that are known to negatively impact reproductive functions. As such, the use of BPA in the manufacturing industry has slowly been replaced by analogs, including bisphenol S (BPS) and bisphenol F (BPF), despite limited knowledge available regarding their impact on health and their safety. The following study investigates the effects of BPA, BPS and BPF at a concentration of 0.5 g/mL and 50 g/mL on bovine granulosa cell apoptosis, with the ultimate goal of determining how they may impact oocyte competence and, thus, overall fertility. The underlying hypothesis is that bisphenols disrupt the granulosa cell environment surrounding the oocyte inducing excessive apoptosis via the intrinsic mitochondrial pathway. To test this hypothesis, apoptosis was measured following a time- and dose-dependent exposure to all three bisphenols by flowcytometry paired with annexin V/PI staining as well as by quantification of key genes belonging to the intrinsic apoptotic pathway both at the mRNA and protein levels. The results of this study report that BPA and BPF reduce cell viability through reduced cell counts and increased apoptosis. This increase is due, in part, to the induction of apoptotic genes of the intrinsic pathway of apoptosis. Additionally, this study also suggests that BPS may not act on the intrinsic mitochondrial apoptotic pathway in bovine granulosa cells. Overall, this study allows us to establish potential apoptotic pathways activated by bisphenols as well as compare the relative apoptotic activities of BPA to its most widespread analogs.